Análise do mercado de trabalho e carreira nas indústrias criativas do estado de São Paulo - Bendassolli, Pedro Fernando (2015)
The purpose of this investigation is to extend the concept of boundary-less careers to understanding the careers of artists selected from a core of São Paulo creative industry segments. Furthermore, it also attempted to map these segments’ occupational characteristics. To this end, the investigation combines qualitative techniques and semi-structured interviews with twenty artists belonging to the relevant creative core, as well as a quantitative assessment providing a descriptive analysis of micro-data drawn from the PNAD/IBGE 2006 survey. The results of the statistical analysis show that the analyzed creative occupations core represents a mere 1.5 percent of occupations in the State of São Paulo, and that 65 percent of those concern self-employment, with 70 percent of occupants making up to three minimum wages/month. The qualitative results show that artists tend to join the world of arts early, are usually self-taught, use activities diversification as a career strategy, or even resort to double careers. In addition, they are affectively more committed to work, which they differentiate from employment. Among the market’s negative traits lie financial fluctuation and instability and a hard struggle for reputation and professional recognition. The study also offers certain hypotheses for later investigation.